Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 130739 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Pulsatilla rubra (Lam.) Jord.", "TaxonKey is Pulsatilla vernalis (L.) Mill.", "TaxonKey is Quercus faginea Lam.", "TaxonKey is Quercus ilex L.", "TaxonKey is Quercus lusitanica Lam.", "TaxonKey is Quercus rotundifolia Lam.", "TaxonKey is Ranunculus batrachioides subsp. brachypodus G.López", "TaxonKey is Ranunculus bupleuroides Brot.", "TaxonKey is Ranunculus seguieri Vill.", "TaxonKey is Ranunculus serpens Schrank", "TaxonKey is Rhamnus pumila Turra", "TaxonKey is Rumex rupestris Le Gall", "TaxonKey is Salix repens", "TaxonKey is Sambucus racemosa L.", "TaxonKey is Santolina oblongifolia Boiss.", "TaxonKey is Saponaria caespitosa Bivona", "TaxonKey is Sarcocornia fruticosa (L.) A.J.Scott", "TaxonKey is Saxifraga felineri P.Vargas", "TaxonKey is Saxifraga babiana T.E.Díaz & Fern.Prieto", "TaxonKey is Saxifraga longifolia Ten.", "TaxonKey is Saxifraga losae Sennen", "TaxonKey is Saxifraga praetermissa D.A.Webb", "TaxonKey is Sedum aetnense Tineo", "TaxonKey is Sedum alpestre Vill.", "TaxonKey is Sedum nevadense Coss.", "TaxonKey is Selinum carvifolia (L.) L.", "TaxonKey is Sibbaldia procumbens L.", "TaxonKey is Sideritis hyssopifolia Georgi", "TaxonKey is Sideritis borgiae subsp. borgiae", "TaxonKey is Sideritis lurida J.Gay", "TaxonKey is Silene acutifolia Link ex Rohrb.", "TaxonKey is Soldanella alpina subsp. cantabrica Kress", "TaxonKey is Spartina maritima (Curtis) Fernald", "TaxonKey is Spergula viscosa Lag.", "TaxonKey is Spergularia heldreichii E.Simon", "TaxonKey is Suaeda splendens (Pourr.) Gren. & Godr.", "TaxonKey is Suaeda vera Forssk. ex J.F.Gmel.", "TaxonKey is Taxus baccata L.", "TaxonKey is Thalictrum alpinum L.", "TaxonKey is Thymus caespititius Brot.", "TaxonKey is Trifolium rubens L.", "TaxonKey is Utricularia ×australis R.Br.", "TaxonKey is Verbascum barnadesii Vahl", "TaxonKey is Veronica mampodrensis Losa & P.Monts.", "TaxonKey is Chamaerops humilis L.", "TaxonKey is Myrtus communis L.", "TaxonKey is Rhamnus alaternus L.", "TaxonKey is Tetraclinis articulata (Vahl) Mast.", "TaxonKey is Ulmus minor Mill.", "TaxonKey is Maytenus senegalensis subsp. europaeus (Boiss.) Rivas Mart. ex Güemes & M.B.Crespo" ] } ] } The dataset includes 130739 records from 109 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000578-150304104939900/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences